2009
DOI: 10.1097/mco.0b013e32832a7902
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation, nutritional status and survival in patients with cancer

Abstract: 2 Purpose of the ReviewThere is now good evidence in humans that a chronic systemic inflammatory response results in the cardinal features of cancer cachexia, principally the progressive loss of weight (in particular lean tissue). This review examines the role of recent simple objective systemic inflammation-based scores in predicting reduction of nutritional status and survival. Recent findingsThe most common measure of the systemic inflammatory response in cancer patients has been an elevated C-reactive prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
708
4
20

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 891 publications
(742 citation statements)
references
References 33 publications
10
708
4
20
Order By: Relevance
“…In several studies, high inflammatory parameters (CRP, alpha and gamma globulins, neutrophil lymphocyte ratio (NLR), complement C3-C4) were found and associated with reduced overall survival in patients with different cancers including lung cancers (Shimada et al, 2003;Canna et al, 2005;Kaya et al, 2013;Zheng et al, 2013;Dai et al, 2014;Soliman et al, 2014). Increasing synthesis of acute phase proteins and interleukins and tumor necrosis-related hypoxia may be the mechanisms underlying this increased inflammation (McMillan et al, 2009). In our study, level of white blood cell was an independent predictor of mortality in patients with lung adenocarcinoma (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, high inflammatory parameters (CRP, alpha and gamma globulins, neutrophil lymphocyte ratio (NLR), complement C3-C4) were found and associated with reduced overall survival in patients with different cancers including lung cancers (Shimada et al, 2003;Canna et al, 2005;Kaya et al, 2013;Zheng et al, 2013;Dai et al, 2014;Soliman et al, 2014). Increasing synthesis of acute phase proteins and interleukins and tumor necrosis-related hypoxia may be the mechanisms underlying this increased inflammation (McMillan et al, 2009). In our study, level of white blood cell was an independent predictor of mortality in patients with lung adenocarcinoma (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition and inflammation suppress albumin synthesis and affect the survival of cancer patients 31, 39. In fact, it has been reported that hypoalbuminemia in cancer patients is associated with poor outcome 31, 38, 39. In fact, patients in the high GAR group (>0.80) had decreased serum albumin level and poor outcome after curative surgery compared as low GAR group (Table 2 and Figure 2).…”
Section: Discussionmentioning
confidence: 92%
“…In addition, these cytokines induce the production of various acute‐phase proteins and these proteins which are contained in the serum globulin fraction 24, 25, 26, 27, 28. Interestingly, it has been reported that these cytokines and acute‐phase proteins are associated with the prognosis of cancer patients 29, 30, 31, 32, 33, 34, 35, 36, 37. These facts suggest that an elevated serum globulin level may reflect an enhancement of tumor progression and distant metastasis due to an alteration of tumor cell biology and suppression of antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, patients with an elevated C-reactive protein were assigned a modified GPS score (mGPS) of 1 or 2 depending on the absence or presence of hypoalbuminaemia 20 . The rationale for the development of the GPS has been described previously 8 and the prognostic value of the combination of C-reactive protein and albumin has validated in a variety of common solid tumours 21 .…”
Section: Methodsmentioning
confidence: 99%